RELATIONSHIP BETWEEN HOSPITAL LEADERSHIP STYLE WITH EMPLOYEE PERFORMANCE AT GENERAL HOSPITAL IN THE COVID-19 PANDEMIC PERIOD - Raras Merbawani; Lasiyati Yuswo Yani; asef wildan munfadlila (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2021)
The development of an agency is the duty of a leader to make it happen. In this case the leader needs qualified subordinates or employees to realize this vision. Leaders must be able to influence their employees to be responsible for completing their work. The purpose of this study was to identify the relationship between leadership style and employee performance in Sidoarjo Dr Soekandar Hospital Mojosari Hospital. The design in this study was cross-sectional. This study's population were all employees of the Mojosaris hospital as many as 90 employees; the sampling technique was total sampling. The sample in this study is Mojosari hospital employees totaling 90 employees. The crosstabs test results using SPSS 25.0 showed that more dominant in using the strategic leadership style. Results can be seen that respondents with sufficient performance. The leadership style in the Moderate category was more than the leadership style in the high categories. 16 (57%) of respondents. Meanwhile, respondents with good performance. The high category's leadership style was far more than the leadership style in the medium category 47 (75%) of respondents. So it can be concluded that the better the leadership applied by the head of the hospital. The better the quality and quantity of employee performance at the hospital. In advancing the institution, cooperation between leaders and employees is needed. Leaders must be able to understand the character of employees and the conditions they face in order to create an effective leadership style. The implementation of an effective leadership style can improve the quality and quantity of employee performance.